Antioxidant Status In Effluent Treated Grains Of Vigna radiata - Shakila, P Baby; Usha, K (Journal of Agriculture and Environment, 2013)
Effect of tannery effluent on the growth and anti oxidant status of Vigna radiata (L.) R. Wilcz. was investigated in 2009. Plants were grown in two dilutions and the results were compared with the control plants grown simultaneously in the same condition. Enzymic and non-enzymic antioxidants were analyzed in the grains. The antioxidant enzyme superoxide dismutase was found increased when the concentration of the effluent increased. Where, the concentration of catalase, peroixidase, glutathione system, polyphenol oxidase, ascorbic acid, tocopherol, polyphenol, lycopene and carotenoid were decreased when the concentration of the effluent increased. This study proves that Vigna radiata should not be grown in the soil having highest level of tannery effluent for maintaining human health and the environment. The Journal of Agriculture and Environment Vol:12, Jun.2011, Page 22-26 DOI: http://dx.doi.org/10.3126/aej.v12i0.7559